2008
DOI: 10.1002/app.25083
|View full text |Cite
|
Sign up to set email alerts
|

Improving the antibacterial activity of cotton fabrics finished with triclosan by the use of 1,2,3,4‐butanetetracarboxylic acid and citric acid

Abstract: For producing antibacterial textiles, the conventional finishing processes have high productivity and low processing costs, but textiles finished in these ways exhibit low durability against laundering. Therefore, cotton fabrics were bleached with hydrogen peroxide, finished with triclosan, and then treated with polycarboxylic acids such as 1,2,3,4-butanetetracarboxylic acid (BTCA) and citric acid (CA) as crosslinking agents to provide durable antibacterial properties. The surface of fibers treated with BTCA h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 25 publications
0
50
0
2
Order By: Relevance
“…Several studies have shown that cellulosic esterification by polycarboxylic acids takes place in two phases. In the first phase a cyclic anhydride is formed (Yang et al 1998), which forms an ester with the hydroxyl group (-OH) in the cellulose macromolecule (Orhan et al 2009;Sauperl and Stana-Kleinschek 2010). This is followed by formation of a second anhydride that subsequently reacts with another cellulose hydroxyl.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that cellulosic esterification by polycarboxylic acids takes place in two phases. In the first phase a cyclic anhydride is formed (Yang et al 1998), which forms an ester with the hydroxyl group (-OH) in the cellulose macromolecule (Orhan et al 2009;Sauperl and Stana-Kleinschek 2010). This is followed by formation of a second anhydride that subsequently reacts with another cellulose hydroxyl.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that cellulosic esterification by polycarboxylic acids takes place in two phases. According to Yang & Xu (1998), in the first phase a cyclic anhydride is formed, which forms an ester with the hydroxyl group (-OH) in the cellulose macromolecule (Orhan et al, 2009;Sauperl & Stana-Kleinschek, 2010). This is followed by formation of a second anhydride that subsequently reacts with another cellulose hydroxyl.…”
Section: Microgel Incorporation To Previously Non-activated Cottonmentioning
confidence: 99%
“…As the widespread use of triclosan could represent a potential risk in terms of the development of resistant microorganisms [39], strong binding to solid surfaces with subsequent controlled release is important. Triclosan has therefore been applied to cellulose fibers in combination with polycarboxylic acids as crosslinking agents [40]. The application of polycarboxylic acid to fibers previously finished with triclosan enhances the washing durability of the antimicrobial coating.…”
Section: Halogenated Phenolsmentioning
confidence: 99%